Information technology of scaling cloud app with variable load peaks - Савчук, Тамара Олександрівна; Козачук, Андрій Валерійович (Technology audit and production reserves, 2015)
One of the main advantages of cloud computing is ability to adapt to rapid changes of user count via web app scaling that allows deploying computing resources only when there is a demand. Modern systems of web app automatic scaling run base on reactive scaling rules. Such rules perform initialization of a scaling process when some app metric, for example CPU load, reaches a critical value. This approach in efficient in general, but in case of short and intense load peaks, there can be problems in cloud app functioning during time period between starting of cloud app scaling and final deployment of computing resources. Developed information technology removes this disadvantage by forecasting of cloud app usage and deploying computing resources in advance. Forecasting of cloud app using is the core idea of proactive scaling. Developed information technology of cloud app scaling is based on combination of reactive and proactive scaling. Comparison of cloud app efficiency shows that using of developed information technology of cloud app scaling allows increasing general web app efficiency by 8 %. This allows cutting spending on cloud application hosting and making cloud application more responsive.